Sailing to Sarantium - Kay, Guy Gavriel (Kay, Guy Gavriel. Sarantine mosaic ;, 2010)
After being given a talisman and tasked with carrying out a mission for the queen in the city of Sarantium, Crispin's talent for making mosaics leads him to discover a source of great power that may be his only hope of survival.